SURGICAL CONSIDERATIONS IN PATIENTS WITH LUMBAR SPINAL ROOT ANOMALIES - (:unkn) unknown (STOCKTON PRESS, 1992)
Lumbosacral nerve root anomalies are rare and can cause diagnostic confusion. In this report we present 12 patients with lumbar root anomalies. Emphasis is placed on preoperative neuroradiological evaluation and the surgical implications of these anomalies.
Keywords: LUMBOSACRAL NERVE ROOTS; ROOT ANOMALIES; MYELOGRAPHY; COMPUTERIZED TOMOGRAPHY; OPERATIVE SURGERY